Signing electronic contracts. - Molnar, David
Electronic commerce faces the problem of signing electronic contracts. Three approaches for handling electronic contracts include 1) no trusted third party protocols, 2) strongly-trusted third party protocols and 3) weakly-trusted third party protocols. A secondary problem facing electronic commerce is self-enforcing contract design.
Keywords: Computing milieux; Legal aspects of computing; Computers and society; Economics; Human factors; Legal aspects